1984
DOI: 10.1136/jcp.37.6.711
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of Clostridium difficile by direct detection of volatile organic acids from primary isolation media.

Abstract: The procedures described simplify the measurement of chemotaxis. Elimination of visual counting facilitates replication of the procedure and allows a larger number of samples to be tested in a short time.We had anticipated that counting all the cells crossing the membrane rather than a random sample of them would reduce the variance of the test readings. This did not prove to be the case, however; most of this variance seemed to be due to differences between the filters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Potvliege et al used GLC to detect isocaproic acid produced by C. difficile and reported a sensitivity of 61% and a specificity of 95% (24). Other researchers have used more complicated GLC procedures but did not achieve high sensitivity (3,4,17). Pepersack et al used a more sensitive chromatograph and reported a sensitivity of 100% and a specificity of 92% (23).…”
Section: Discussionmentioning
confidence: 99%
“…Potvliege et al used GLC to detect isocaproic acid produced by C. difficile and reported a sensitivity of 61% and a specificity of 95% (24). Other researchers have used more complicated GLC procedures but did not achieve high sensitivity (3,4,17). Pepersack et al used a more sensitive chromatograph and reported a sensitivity of 100% and a specificity of 92% (23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the concentrations of cycloserine and cefoxitin and the type of basal medium affect the recovery rate and the phenotypic properties (e.g., the intensity of the fluorescence) exhibited by the organism (130,131). Some of the unusual metabolic products (e.g., p-cresol and isocaproic acid) produced by C. difficile have been suggested as markers for the organism (54, 84,129,134,150,171,175,182). The detection of these substances is not specific enough to be used as a marker for clinical diagnosis.…”
Section: Isolation and Identification Of The Organismmentioning
confidence: 99%
“…In addition, the concentrations of cycloserine and cefoxitin and the type of basal medium affect the recovery rate and the phenotypic properties (e.g., the intensity of the fluorescence) exhibited by the organism (130,131). Some of the unusual metabolic products (e.g., p-cresol and isocaproic acid) produced by C. difficile have been suggested as markers for the organism (54,84,129,134,150,171,175,182). The detection of these substances is not specific enough to be used as a marker for clinical diagnosis.…”
Section: Counterimmunoelec-mentioning
confidence: 99%